Teachers’ Performance Appraisal: The Reality of Unified Evaluation for Education Services Officer Implementation in Malaysian Primary Schools - Nor Azuanee Mukhtar; Mohd Asri Mohd Noor (International Business Education Journal, 2024)
The aim and objective of this article is to explore the issues and challenges of performance appraisals from the views and perceptions of teachers in selected Malaysian primary schools based on The Unified Evaluation for Education Services Officer’s documents also known as Penilaian Bersepadu Pegawai Perkhidmatan Pendidikan (PBPPP). The documents are used as formal documents in teachers’ performance appraisal evaluation since 2016. This article attempts to understand the issues of the implementation based on the teachers’ experiences on the evaluation conducted by educational leaders in their schools. Performance appraisal is always stigmatized with the element of bias, and it is crucial to have clear perspectives of the teachers’ true experiences on the positional of this claim. For the analysis, a single explanatory case study based on qualitative methodology was implemented by adapting deductive thematic analysis method. In order to collect transparent data, semi-structured interview questions were designed using the formal appraisal evaluation form as reference. The selection of informants was using purposive sampling which involved five teachers with working experience between five to 30 years. The analysed data from the interview transcriptions and formal documents were divided into three themes: practice, implementations, leaders’ capabilities, and teachers’ experiences. Through the data, it is interesting to find that the contrast between the documents implementation and the actual practice carries out in schools. Halo effect is one of the leadership biases which frequently occurred based on the data collected. This study could be a reference to the school and educational leaders to thoroughly examine the reality and capabilities of the school leaders to reduce bias in education service officers’ performance appraisal.